Rhetoric of persuasion in religious talk - Abdul Malik, Badrol Hisham; Abdullah, Muhd Alif Redzuan; Wan Ahmad, Wan Noor Aini (Human Resource Management Academic Research Society, 2023)
This study is a descriptive study that uses Modern Rhetoric Theory by Enos and Brown (1993) as the basis of the study. Content analysis methods are used to examine texts textually and contextually. The main focus or objective of the study is to identify the rhetoric of persuasion found in religious discourses that are usually used in the field of advertising. This study as a whole was made to examine the effectiveness of language aspects and various techniques of persuasion found in religious talks. Analyzing the rhetoric of persuasion to see the important role of rhetoric in the speeches chosen by the researcher as research data to see the art of language in informing, persuading, and influencing the listener's thinking. The rhetoric of persuasion that is processed as best as possible in influencing the audience is divided into two, namely rational persuasion and irrational persuasion. In other words, the rhetoric of persuasion in religious talks is an important element used by experts in enlivening the atmosphere and influencing the listener's thinking.